Answer:
(1,4)
Step-by-step explanation:
if u substitute these numbers u can find out that these numbers make the solution.
hope this helps
Answer:
f(-14) = -6
f(-4) = 6
f(12) = 6
f(0) = -3
negative
Step-by-step explanation:
f(-14) = -6
This is because when x is -14, y is -6, as seen in the graph
f(-4) = 6
This is because when x is -4, y is 6, as seen in the graph
f(12) = 6
This is because when x is 12, y is 6, as seen in the graph
f(0) = -3
This is because when x is 0, y is -3, as seen in the graph
is f(4) positive or negative?
negative
This is because when x is 4, y is -6, as seen in the graph
the answer is five point six five, 5.65
Answer:
good to be a 2yo.bbkgky8ckd7fej
Use the quadratic formula .
x^2-2x+11=0
a=1
b=-2
c=11
x=-2+- (-2)^2-4*1*11 divided by 2
x=2+- the square root of -40 divided by 2
There is no real solutions